2016
DOI: 10.17295/dcd.08733
|View full text |Cite
|
Sign up to set email alerts
|

HAYVAN VARLIĞINA GÖRE ÇANAKKALE BİYOGAZ POTANSİYELİNİN TESPİNE YÖNELİK BİR ÇALIŞMA-A STUDY FOR DETERMINATION OF BIOGAS POTENTIAL in ÇANAKKALE, ASSETS BY ANIMALS

Abstract: Currently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…The previous studies have revealed the BPs of different years have ranged between 9.7×10 7 m 3 and 1.8×10 7 m 3 respectively by Ilgar (2016) and Özpınar (2018). The discrepancies have arised from two main reasons in these studies.…”
Section: Total Bp Of çAnakkale Provincementioning
confidence: 90%
See 1 more Smart Citation
“…The previous studies have revealed the BPs of different years have ranged between 9.7×10 7 m 3 and 1.8×10 7 m 3 respectively by Ilgar (2016) and Özpınar (2018). The discrepancies have arised from two main reasons in these studies.…”
Section: Total Bp Of çAnakkale Provincementioning
confidence: 90%
“…al (2017) to determine animal waste energy potential; Polat-Bulut and Topal-Canbaz (2019) identified the BP for Sivas province, and energy potential of Samsun province from animal manure has been studied by Zenk (2019) . Furthermore, there is a limited number of studies that was conducted in Çanakkale Province (Ilgar, 2016;Özpınar, 2018), which is located within in the Marmara Region that remarked to involve major part of presently installed power. However, mentioned studies have investigated the BP of Çanakkale at upper scales of province and district level, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Biyogaz ise biyokütle kaynaklarından elde edilen önemli bir biyoyakıttır (İlkılıç ve Deviren, 2011). Biyogaz, dışa bağımlılığı azaltan, bölgenin kalkınmasına katkı sağlayan, ekolojik yapıya zarar vermeyen sürdürülebilir bir enerji kaynağıdır (Ilgar, 2016 (Yağlı ve Koç, 2019).…”
Section: Introductionunclassified
“…Dairy and meat cooperatives and the renewable energy investors show particular interest in biogas production but there are still no biogas plants operating in Burdur. There are a number of studies for estimating the biogas potential in different provinces in Turkey from variety of wastes [30][31][32][33], however there are no studies available for biogas potential for Burdur Province and its districts. Therefore, this study attempts to identify the biogas potential of Burdur considering animal manure capacity using recent data to assess the utilization of the waste in terms of biogas production, energy generation, organic fertilizer production and its benefits in terms of public health and comfort for promoting the biogas investments.…”
Section: Introductionmentioning
confidence: 99%